2021
DOI: 10.1155/2021/6726622
|View full text |Cite
|
Sign up to set email alerts
|

Review of Anopheles Mosquito Species, Abundance, and Distribution in Ethiopia

Abstract: Background. Malaria is a major mosquito-borne disease in Ethiopia, and it is one of the leading causes of morbidity and mortality. Plasmodium falciparum and P. vivax are the two malaria-causing parasitic species commonly known to cause human malaria in Ethiopia. To better manage and control vectors transmitting malaria parasites, the abundance, distribution, and updated annotated list of Anopheles species present in Ethiopia are very important. Methods. In order to compile a list of the species recorded in Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…In line with the present study, various workers reported that An. gambiae complex was the most abundant species in different parts of Africa and Ethiopia [4,6,7,[26][27][28][29]. e better occurrence of the Anopheles species in January could be because the low temperature of the study area is not optimum for frequent adult emergence and the larvae stay a long time in breeding habitats [17][18][19][20]30].…”
Section: Discussionmentioning
confidence: 96%
“…In line with the present study, various workers reported that An. gambiae complex was the most abundant species in different parts of Africa and Ethiopia [4,6,7,[26][27][28][29]. e better occurrence of the Anopheles species in January could be because the low temperature of the study area is not optimum for frequent adult emergence and the larvae stay a long time in breeding habitats [17][18][19][20]30].…”
Section: Discussionmentioning
confidence: 96%
“…funestus and An. nili , were incriminated as vectors of malaria [ 20 ]. Anopheles arabiensis is the primary malaria vector in most malaria-endemic areas [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…funestus, and An. nili, were incriminated as vectors of malaria [19]. Anopheles arabiensis is the primary vector in most malaria-endemic areas [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, its abundance, host preference, and Plasmodium infection rate vary across ecological gradients and epidemiological settings [21][22][23][24]. Anopheles pharoensis is of secondary importance [19,22], with An. funestus and An.…”
Section: Introductionmentioning
confidence: 99%